2021
DOI: 10.1002/pd.5977
|View full text |Cite
|
Sign up to set email alerts
|

The many etiologies of nonimmune hydrops fetalis diagnosed by exome sequencing

Abstract: Objective: To explain the importance of identifying an etiology for the pathological finding of nonimmune hydrops fetalis (NIHF) and to explore the impact of exome sequencing in recurrent NIHF. In addition, we present two cases of pregnancies affected with recurrent NIHF, in which genetic investigation was advantageous.Methods: Our study aimed to investigate the genetic background, if available, of all fetuses with NIHF referred to our tertiary medical center from January 2013 to August 2020. We summarized the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Six reports examined specific phenotypic sub-groups from previously published larger cohorts, [23][24][25][26][27][28] hence were not separate studies. These were excluded from the overall meta-analysis of incremental yield and the subgroup analysis by case selection, to avoid double-counting of cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six reports examined specific phenotypic sub-groups from previously published larger cohorts, [23][24][25][26][27][28] hence were not separate studies. These were excluded from the overall meta-analysis of incremental yield and the subgroup analysis by case selection, to avoid double-counting of cases.…”
Section: Resultsmentioning
confidence: 99%
“…After screening by title and abstract, and retrieving full text reports, 148 articles were assessed, of which 72 reports from 66 studies were deemed eligible and included in the final review (Figure 1, Table 1). Six reports examined specific phenotypic sub‐groups from previously published larger cohorts, 23‐28 hence were not separate studies. These were excluded from the overall meta‐analysis of incremental yield and the subgroup analysis by case selection, to avoid double‐counting of cases.…”
Section: Resultsmentioning
confidence: 99%
“…Except for aneuploidies, a singlegene disease is another important genetic factor that can result in NIHF. Recent studies, in which ES was used to diagnose unexplained fetal hydrops, showed a diagnostic yield of 29%∼50% [17][18][19][20]. In our study, the lower detection rate of ES (16.7%) might be due to the fact that most of the cases were primary hydrothorax, which was caused by erroneous lymphatic formation and reabsorption and was rarely associated with genetic diseases.…”
Section: Discussionmentioning
confidence: 49%
“…With the application of exome sequencing (ES), an increasing variety of genetic disorders have been diagnosed [16]. Several recent studies indicated that ES could identify diagnostic genetic variants in 29%∼50% of unexplained NIHF cases [17][18][19][20]. It suggested that further detailed genetic evaluations of NIHF might be necessary to guide intrauterine interventions.…”
Section: Introductionmentioning
confidence: 99%
“…10 Such information changes counseling, since standard testing with CMA has lower yield for these diagnoses and also highlights the importance of collaboration and combining data from multiple cohorts. Other series from around the world are included in the second special issue to be published in June, and report sequencing yield for a variety indications of including hydrops, cardiac defects and renal anomalies, [11][12][13][14][15][16] again showing significant incremental diagnostic yields. Another interesting report on Non-Immune Hydrops Fetalis (NIHF) by Reytan and colleagues describes a fetus with NIHF with compound heterozygous deletions of PIEZO1.…”
mentioning
confidence: 99%